2021
DOI: 10.1101/2021.12.09.471892
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the Connection between Autophagy and Heat-Stress Tolerance in Drosophila melanogaster

Abstract: Autophagy is a physiological process that facilitates the recycling of intracellular cytosolic components as a response to diverse stressful conditions. By increasing the turnover of damaged structures and clearance of long-lived and larger protein aggregates, the induction of autophagy increases tolerance to abiotic stress in a range of organisms. However, the contribution of this process to heat-tolerance of insect models remains poorly studied to date. Here, we report that rapamycin exposure in Drosophila m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…As TOR is a master regulator of growth, which detects cellular levels of amino acids and is inactivated by low levels of amino acids (Saxton and Sabatini 2017), we assumed that both isoleucine deprivation and rapamycin achieved nicotine resistance through TOR suppression. However, other studies have shown that rapamycin treatment improves heat tolerance of wildtype flies (Willot et al 2023) and can improve the maximum thermal temperature (CTmax) withstood by DGRP flies (Rohde et al 2021). We therefore anticipated that short term isoleucine deprivation would also increase heat tolerance in our flies, but it did not.…”
Section: Discussionmentioning
confidence: 99%
“…As TOR is a master regulator of growth, which detects cellular levels of amino acids and is inactivated by low levels of amino acids (Saxton and Sabatini 2017), we assumed that both isoleucine deprivation and rapamycin achieved nicotine resistance through TOR suppression. However, other studies have shown that rapamycin treatment improves heat tolerance of wildtype flies (Willot et al 2023) and can improve the maximum thermal temperature (CTmax) withstood by DGRP flies (Rohde et al 2021). We therefore anticipated that short term isoleucine deprivation would also increase heat tolerance in our flies, but it did not.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a cellular process that involves the degradation and recycling of cellular components, and it has been linked to increased tolerance to a range of abiotic stressors, including heat stress, in various ectothermic organisms. Flies exposed to heat stress exhibit protein aggregation, triggering an autophagy-related response, while rapamycin feeding induces local autophagy in the gut and enhances heat-stress tolerance [34]. sHsps (Small heat shock proteins) belong to the HSPs family, with a molecular weight of 15-40 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…Data accessibility. Datasets supporting this article are publicly available: https://doi.org/10.5061/dryad.4qrfj6qf9 [78].…”
mentioning
confidence: 99%